AI-Augmented HRM and Employee Performance: Digital Trust Mediation and AI Readiness Moderation - Arien Anjar Puspitosari Suharso; Andi Nu Graha (Jurnal Publikasi Ilmu Manajemen, 2026)
This study aims to examine the effect of AI-Augmented Human Resource Management (AI-Augmented HRM) on employee performance by investigating the mediating role of digital trust and the moderating role of AI readiness. A quantitative explanatory approach with a cross-sectional design was employed involving 165 employees who had experienced AI-supported HR practices, selected through purposive sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that AI-Augmented HRM has a positive and significant effect on employee performance and digital trust, while digital trust significantly improves employee performance and partially mediates the relationship between AI-Augmented HRM and employee performance. AI readiness also has a positive effect on employee performance and significantly strengthens the influence of AI-Augmented HRM on employee performance. These findings imply that organizations should complement AI adoption with transparent digital governance, trust-building mechanisms, employee AI competency development, human oversight, and continuous organizational support to achieve sustainable performance improvement.